استعمال وسائل اللافتات والملصقات لتسهيل الطلاب على تعلم اللغة العربية - Cut Keumalawati (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
This research aims to find out what are the means of banners and posters, and to know how to use the means of banners and posters, and to know how the students' results after using the means of banners and posters. The results of the research in this thesis are: (1) The means of banners and posters are educational aids as devices, tools and materials used by the teacher to improve the teaching and learning process, a combination of a clear visual, flashy, and attractive structure with the intention of attracting the attention of passers-by. Banners and posters influence behaviour, and the value system is combined to change or do something. (2) And how to use the means of signs and posters to facilitate the students to learn the Arabic language in two ways: (a) It is used as part of the teaching and learning activities, and in this case the posters are used when the teacher and a poster explain to the students (posters as a means of learning), and so do the students in the educational materials Using posters provided by teachers. The label used must be relevant to the purpose and material. (b) Use outside of learning to motivate students, as a warning, advocacy, publicity or call to do something positive, and to build social values ​​and diversity. (3) As for the results of the students after using the means of signs and posters, they are higher and better without using them. This is based on the results in the hypothesis test that the statistical t-score = 3,854 is greater than the result of the moral level = 1.68 and this indicates that the use of means of signs and posters to facilitate students to learn the Arabic language is effective and has the best effect for students from the middle school Dar Al-Mutaqin Trienggadeng.